KAFA’AH DALAM RELASI SUAMI ISTRI SESAMA SANTRI UNTUK MEWUJUDKAN KELUARGA SAKINAH - Jufri, Muhammad (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2024)
This study explores the relationship between husband and wife, both of whom are pesantren alumni, in building a sakinah (harmonious) family in Temuasri Village, Sempu District, Banyuwangi Regency. As alumni of Islamic boarding schools, santri couples possess religious knowledge, social values, and life experiences that significantly contribute to maintaining household harmony. Despite coming from different pesantren backgrounds, differences in routines and habits can be resolved through practices such as mutual service, support, and the application of pesantren teachings in daily life. These principles include strengthening tarbiyah, reminding each other of goodness, and fulfilling respective rights and responsibilities. The concept of kafa’ah (compatibility) in the aspect of religion also plays a crucial role in ensuring family tranquility. A deep understanding of religious teachings provides a strong foundation for couples to face household challenges and social influences. By practicing pesantren values such as communal prayer, Qur'anic recitation, and respecting differences, santri couples can foster harmonious relationships. Furthermore, their experiences in pesantren, which teach adaptability to various characters and cultures, help them manage differences and strengthen family bonds. In conclusion, the combination of religious knowledge, pesantren experiences, and the application of kafa’ah principles enables santri couples to achieve a sakinah family. This harmony not only inspires the couples themselves but also serves as an example for the surrounding community on the importance of religious values in family life.